DISCLOSURE OF BUSINESS VALUE INFORMATION IN THE FINANCIAL STATEMENTS (REPORTING OF THE COMPANY) - Y. Kharina (Publishing House of the State University of Management, 2017)
For the purpose of preparation reporting of the company and disclosure of business value information the integrated model is presented and the elements of information providing system are proved. Accounting and control, analytical and evaluation providing of business management are identified.